Nature protocols
Nature Protocols is an interactive online resource for experimental and laboratory protocols for bench researchers primarily in biology and chemistry. Protocols are presented in a 'recipe' style providing step-by-step descriptions of procedures that users can take to the lab bench and immediately apply in their own research. Protocols on the site are fully searchable and organized into logical categories to be easily accessible. Together, 'Nature Protocols' and the interactive 'Protocols Network' create a dynamic forum for scientists to upload and comment on protocols.